KETIMPANGAN AKSESIBILITAS DAN INFRASTRUKTUR PARIWISATA: PENERAPAN KERANGKA KONEKTIVITAS PAGE UNTUK MENGOPTIMALKAN POTENSI DAERAH DI ACEH BARAT, INDONESIA - Cut Asmaul Husna; Sri Wahyu Handayani; Herizal Herizal (LPPM Universitas Abdurrab, 2026)
This study aims to analyze disparities in tourism accessibility and infrastructure in West Aceh Regency and their impacts on destination attractiveness by employing Stephen J. Page’s Tourism Accessibility and Connectivity framework. The research is motivated by stagnant tourist growth and the uneven distribution of tourism-supporting infrastructure, which constrain the optimization of West Aceh’s tourism potential. An exploratory case study design using a qualitative approach was adopted. Data were collected through field observations, in-depth interviews, analysis of local development policy documents, and secondary data from the Central Bureau of Statistics (BPS), the Tourism Office, and the Public Works Agency. The findings indicate that more than 40% of the district road network is either damaged or unpaved, public transportation services do not reach major tourist destinations, and formal accommodation facilities are entirely concentrated in Johan Pahlawan Subdistrict. These conditions render access to key destinations such as Pungki Waterfall, Pocut Baren’s Tomb, and the National Hero Teuku Umar’s Grave difficult, costly, and non-inclusive. Such disparities have directly contributed to low tourist arrivals, short lengths of stay, and stagnant local economic growth. This study concludes that improving basic infrastructure, integrating transport modes, and strengthening digital connectivity are critical prerequisites for enhancing destination attractiveness and sustainably improving the competitiveness of West Aceh’s tourism sector, thereby underscoring the need for proactive local government involvement in formulating integrated tourism development policies that prioritize peripheral areas and promote equitable accessibility.